Anthalona vandammei sp. nov. from Thailand, a sibling species of Neotropical Anthalona brandorffi (Sinev & Holwedell, 2002) (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y.; Tiang-Nga, Supatra; Sanoamuang, Laorsri (Zootaxa, 2023)
A new rare species of Anthalona Van Damme, Dumont & Sinev, 2011, Anthalona vandammei sp. nov. (Anomopoda: Chydoridae), is described from Thailand. It is a sister species of Neotropical Anthalona brandorffi (Sinev & Holwedell, 2002), sharing three important synapomorphies: (1) postabdomen widening distally in the anterior portion; (2) long posterior setae of valves, with the last setae located at the posteroventral angle of valves; and (3) only two flaming-torch setae of thoracic limbs IV. A. brandorffi and A. vandammei sp. nov. are similar habitually, but can be clearly distinguished by details of thoracic limb morphology. A. vandammei sp. nov. differs from A. brandorffi in (1) limb 1 IDL seta 3 with a basal spine much thicker and much longer than others, (2) longer setae e-f of endite 2 of limb I and (3) scraper 7 of limb II being only slightly smaller than scraper 6. The amphi-Pacific distribution of the brandorffi-clade of Anthalona is explained best by the Boreotropical hypothesis.